Arctic Oil and Gas 2007 - Arctic Council, Arctic Monitoring ans Assessment Programme (AMAP) (Arctic Council, 2008)
The Arctic Councils´s report or assessment had the objective to present a holistic assessment of the environmental, social and economic, and human health impacts of current oil and gas activities in the Arctic, and to evaluate the likely course of development of Arctic oil and gas activities and the potential impacts in the near future.